Geological characteristics and exploration potential of the coal measure gas from Shan 2 of the Shanxi formation in the eastern Ordos Basin - Zhao, Wei-Bo; Zhang, Hui; Shi, Yun-He; Fu, Xun-Xun; Hui, Jie; Jing, Xue-Yuan (Frontiers in Earth Science, 2023)
“Coal measure gas,” excluding tight (low-permeability) sandstone gas, refers in this study to the self-sourcing unconventional natural gas stored in coal, shale, and fine siltstone. It is characterized by various types of occurrences and reservoirs, a distinct cyclic succession of coal measure strata, widely distributed mosaic hydrocarbon accumulations, three types of coal measure gas accumulations, and configurations of vertically multiple-stacked gas-bearing reservoirs. Coal measure gas from Shan 2 can be divided—according to the grain size of sandstone, configurations of sandstone–coal–mudstone association, thickness, and layers—into four types: thick massive sandstone–coal–mudstone (type I), fine siltstone–coal–mudstone (type II), thin sandstone–mudstone–sandstone (type III), and coal–mudstone (type IV). Comprehensive evaluation suggests that the coal measure gas in the Suide-Mizhi area of the southern Ordos Basin presents an important and favorable accumulation option, characterized by coalbed methane, shale gas, and tight gas stored in sandstone–mudstone–coal strata. Therefore, it is essential to conduct full future assessments for the coal beds, shale, and tight gas controlling exploration for the “vertical gas-bearing zone” by three-dimensional exploration.